Determining groundwater quality and its associated human health risk using hydrochemical signatures and some machine learning techniques - Maxwell Anim-Gyampo; Millicent Obeng Addai; Raymond Webrah Kazapoe; Musah Saeed Zango; Stanley Yaw Blankson; Ebenezer Ebo Yahans Amuah; Samuel Dzidefo Sagoe; Belinda Seyram Berdie (Environmental Geochemistry and Health, 2026)

Mitragynine reduces methamphetamine self-administration in rats without disrupting food-maintained responding - Lida Khodavirdilou; Julio D Zuarth Gonzalez; Sushobhan Mukhopadhyay; Nicholas Guadagnoli; Samuel Obeng; Christopher R. McCurdy; Lance R. McMahon; Jenny L. Wilkerson (Psychopharmacology, 2026)
Rationale Kratom ( Mitragyna speciosa ), a plant native to Southeast Asia, has become popular in the United States for its reported ability to treat substance use disorders (SUD). Mitragynine (MG) is the most abundant alkaloid found in kratom. Objectives The present studies evaluated whether MG decreases methamphetamine self-administration under both fixed-ratio (FR) and progressive-ratio (PR) schedules. In a separate cohort we examined whether MG would alter food-maintained responding. Methods Three separate experiments were conducted in male and female adult Sprague–Dawley rats. In Experiment 1, rats self-administered methamphetamine (0.032 mg/kg/infusion, intravenous) under a fixed-ratio (FR) schedule. In Experiment 2, a separate group received food pellets under a FR schedule. In Experiment 3, a different group received methamphetamine (0.032 mg/kg/infusion) under a progressive-ratio (PR) schedule. In all experiments rats received pretreatment with MG (10–56 mg/kg, intraperitoneal) or vehicle 30 min before testing. Behavioral measures included active and inactive lever presses, response rates, and in the case of PR, breakpoints. Results MG dose-dependently reduced methamphetamine delivery under both the FR and PR schedules, with significant decreases in active lever presses, and breakpoints at 32 and 56 mg/kg. Effects were generally comparable in males and females, without significant sex × treatment interaction detected. Conclusions MG decreased methamphetamine-maintained responding at doses that did not affect food-maintained responding, indicating a selective effect on methamphetamine reinforcement relative to natural reward. These findings identify MG as a compound with robust effects on methamphetamine-maintained behavior and support its continued evaluation in preclinical models of methamphetamine use disorder.

First report of Fusarium scirpi causing leaf spot on coconut seedlings in Ghana - Joshua Obeng; Egya Ndede Yankey; Frederick Leo Sossah; Bashiru Adams; Samuel Azupio; Allen Oppong; Joseph Adomako; Esther Afoley Annang; Stephen Larbi-Koranteng; Ophelia Afriyie Obeng; Esther Agyemang Marfo; Owusu Fordjour Aidoo (Crop Protection, 2025)

Sustaining Productivity while Reducing Methane Emission in Calcareous Soils: Implications of Combining Inorganic Fertilizer and Biochar - Agbesi Kwadzo Keteku; Isaac Kodzo Amegbor; Stephen Yeboah; Patricia Amankwaa-Yeboah; Richard Dormatey; Kennedy Agyeman; Mavis Badu Brempong; Ernest Baafi; Maxwell Darko Asante; Allen Oppong; Samuel Aduse Poku; Eric Owusu Danquah; et al. (International Journal of Plant Production, 2025)
A considerable proportion of applied nutrients are adsorbed by the calcite surface of calcareous soils, making them unavailable to plants. A combination of organic amendments and fertilizers can improve nutrient retention and mineralization, and also reduce greenhouse gas (GHG) emissions. A two-years field experiment was undertaken to investigate the impacts of inorganic fertilizer, biochar and silicon on nutrient uptake, growth, yield and post-harvest soil chemistry in calcareous soil using rice ( Oryza sativa L.) as a test crop. The implication of each treatment on methane emissions was also investigated. The combination of NPK, biochar and silicon significantly improved rice growth, yield, P and Si uptake; and post-harvest soil nutrition. Biochar increased soil organic carbon content between 4.2 and 108.5% across the years. An increase from 2.4 to 6.1% was observed in the inorganic fertilizer treatments, 11.4–12.0% for the biochar treatments and 2.5–19.0% for ½NPK + biochar from 2020 to 2021. Maximum grain yield was achieved with the treatment ½NPK + biochar + 100 kg Si ha − 1 which was comparable to NPK + 100 kg Si ha − 1 . Also, the combination of ½NPK + biochar + 50 kg Si reduced CH 4 emissions and produced a comparable yield to NPK + 50 kg Si in both years. While further research is required to explore the effects of the length of time biochar is applied on reducing CH 4 emissions, this study suggests a basis for predicting the impact of biochar on the management of CH 4 emissions in calcareous soils.

Antimicrobial cetylpyridinium chloride causes functional inhibition of mitochondria as potently as canonical mitotoxicants, nanostructural disruption of mitochondria, and mitochondrial Ca2+ efflux in living rodent and primary human cells - Sasha R. Weller; John E. Burnell; Brandon M. Aho; Bright Obeng; Emily L. Ledue; Juyoung K. Shim; Samuel T. Hess; Julie A. Gosse (Food and Chemical Toxicology, 2024)

Engineering design and economic analysis of offshore seaweed farm - Yushun Lian; Samuel Obeng Boamah; Zhenghu Pan; Jinhai Zheng; Wenxing Chen; Gang Ma; Solomon C. Yim (Frontiers in Marine Science, 2024)
As global demand for sustainable biomass and need to mitigate global warming begin to rise, cultivation of seaweed has gained significant attention in recent years due to its potential for carbon recycling. However, limited availability of suitable coastal areas for large-scale seaweed cultivation has led to exploration of offshore environments as a viable alternative. The nature of many offshore environments often exposes seaweed farming systems to harsh environmental conditions, including strong waves, currents, and wind. These factors can lead to structural failures, kelp losses, and significant financial losses for seaweed farmers. The main objective of this study is to present a robust design and numerical analysis of an economically viable floating offshore kelp farm facility, and evaluate its stability and mooring system performance. A numerical method of preliminary designs of the offshore aquaculture systems were developed using the OrcaFlex software. The models were subjected to a series of dynamic environmental loading scenarios representing extreme events. These simulations aimed to forecast the overall dynamic response of an offshore kelp farm at a depth of 50m and to determine the best possible farm design with structural integrity for a selected offshore environment. Furthermore, to assess the economic feasibility of establishing offshore seaweed farms, a comprehensive capital expenses analysis was conducted. The results revealed that, in terms of the kelp farms with the same number of the kelp cultivating lines, the cost of building kelp farms will be strongly affected by the cost of mooring lines. The present study may help to understand the dynamic response and economic feasibility of offshore kelp farms.

Variations in soil chemical properties and growth traits of tissue culture banana under bio-slurry soil amendments in Uganda - Murongo Marius Flarian; Ayuke O. Frederick; Apori Obeng Samuel; Wangai K. John; Wacal Cosmas (Environmental Sustainability, 2023)

The role of bank financing in economic growth and environmental outcomes of sub-Saharan Africa: evidence from novel quantile regression and panel vector autoregressive models - Albert Henry Ntarmah; Yusheng Kong; Anthony Frank Obeng; Samuel Gyedu (Environmental Science and Pollution Research, 2022)

Mechanism and multi-step kinetic modelling of Cr(VI) adsorption, reduction and complexation by humic acid, humin and kerogen from different sources - Samuel Barnie; Jia Zhang; Peter Appiah Obeng; Albert Ebo Duncan; Caspar Daniel Adenutsi; Lin Xu; Honghan Chen (Environmental Science and Pollution Research, 2021)

Spawning habits and embryonic development of the banded lampeye killifish Aplocheilichthys spilauchen ( Duméril 1861) in ex situ fresh and brackish water environments - Isaac Okyere; Juliet Afrah Obeng; Samuel Ayitey; Jouke Rients Van der Zee; Herman Meeus (Journal of Fish Biology, 2021)
Aside from ornamental uses, there is growing interest in using killifishes for a multiplicity of purposes including baitfish and mosquito biocontrol. This experiment explored the spawning habits and embryonic development of the banded lampeye, Aplocheilichthys spilauchen in ex situ freshwater (0.04‰) and brackish water (5.01‰) to ascertain the captive breeding prospects for mosquito control in areas where they occur. Significantly higher number of eggs were laid in the brackish water than the freshwater ( X 2 = 1613.0, P A. spilauchen can be optimally propagated with black mops in brackish water offers a significant step in its use for the mosquito biocontrol programme, as well as other potential uses not yet explored.

Contribution of corncob biochar to the chemical properties of a ferralsol in Uganda - Samuel Obeng Apori; John Byalebeka (Arabian Journal of Geosciences, 2021)

The effects of mitragynine and morphine on schedule-controlled responding and antinociception in rats - Takato Hiranita; Francisco Leon; Jasmine S. Felix; Luis F. Restrepo; Morgan E. Reeves; Anna E. Pennington; Samuel Obeng; Bonnie A. Avery; Christopher R. McCurdy; Lance R. McMahon; Jenny L. Wilkerson (Psychopharmacology, 2019)

Total coliforms, arsenic and cadmium exposure through drinking water in the Western Region of Ghana: application of multivariate statistical technique to groundwater quality - Andrews Obeng Affum; Shiloh Dede Osae; Benjamin Jabez Botwe Nyarko; Samuel Afful; Joseph Richmond Fianko; Tetteh Thomas Akiti; Dickson Adomako; Samuel Osafo Acquaah; Micheal Dorleku; Emmanuel Antoh; Felix Barnes; Enoch Acheampong Affum (Environmental Monitoring and Assessment, 2015)

Growth and reproductive performance of two rabbit breeds reared under intensive system in Ghana - Samuel Obeng Apori; Julius Kofi Hagan; Yaa Doris Osei (Tropical Animal Health and Production, 2015)

The effect of non-genetic factors on the reproductive performance of Sanga and Friesian × Sanga crossbred dairy cattle breeds kept under hot and humid environment - Samuel Obeng Apori; Julius Kofi Hagan (Tropical Animal Health and Production, 2014)